2018
DOI: 10.1007/s40265-018-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Dietary Supplements for Erectile Dysfunction: A Systematic Review and Meta-Analysis

Abstract: Encouraging evidence suggests that ginseng may be an effective herbal treatment for ED. However, further, larger, and high-quality studies are required before firm conclusions can be drawn. Promising (although very preliminary) results have also been generated for some herbal formulations. Overall, more research in the field, adhering to the CONSORT statement extension for reporting trials, is justified before the use of herbal products in ED can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 74 publications
2
24
0
1
Order By: Relevance
“…This is the first report that provides basic mechanistic information concerning CEO and CA-induced dose-dependent relaxation in human and rat CC. The major findings of the present study show that (1) CEO and CA relax human and rat CC in a concentration-dependent manner; (2) NO-cyclic guanosine monophosphate (cGMP) pathway is not involved in the relaxation response to CEO and CA; and (3) CEO and CA improve in vivo erectile function in diabetic rats.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is the first report that provides basic mechanistic information concerning CEO and CA-induced dose-dependent relaxation in human and rat CC. The major findings of the present study show that (1) CEO and CA relax human and rat CC in a concentration-dependent manner; (2) NO-cyclic guanosine monophosphate (cGMP) pathway is not involved in the relaxation response to CEO and CA; and (3) CEO and CA improve in vivo erectile function in diabetic rats.…”
Section: Discussionmentioning
confidence: 66%
“…In the current treatment for ED, phosphodiesterase-5 inhibitors (PDE-5i) are considered the first-line therapy (1). Plant-derived products have been used for the management of ED for a long time, and over 15% of men use natural-based therapies (2). Yohimbine, Korean ginseng, and ginkgo are popular examples used as male sexual performance enhancers in traditional medicine (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginseng is used to promote rejuvenation and longevity, for frailty and stress, weakness and fatigue, both mental and physical (Ogawa‐Ochiai & Kawasaki, ), and as supportive treatment for diabetes, cardiovascular disease and many others (Mancuso & Santangelo, ). Recently, a number of systematic reviews have critically evaluated the clinical evidence for and against the effectiveness of ginseng in a number of conditions, such as erectile dysfunction (Borrelli, Colalto, Delfino, Iriti, & Izzo, ), chronic fatigue (Arring, Millstine, Marks, & Nail, ), hypertension (Lee, Lim, Jun, Choi, & Lee, ), diabetes (Gui, Xu, Xu, & Yang, ), Alzheimer's disease (Wang et al, ) and as an ergogenic aid (Lee, Jung, & Lee, ).…”
Section: Ginseng‐targeted Extractsmentioning
confidence: 99%
“…However, Kim et al [72] reported no benefit of Panax ginseng in a placebocontrolled trial that was based on the Watts Sexual Function questionnaire. Based on a meta-analysis of five clinical studies, Borrelli et al [73] also concluded that Panax ginseng significantly improved erectile function.…”
Section: Panax Ginsengmentioning
confidence: 99%